The Role of Circular RNAs in the Drug Resistance of Cancers - Liu, Xin-Yuan; Zhang, Qi; Guo, Jing; Zhang, Peng; Liu, Hua; Tian, Zi-Bin; Zhang, Cui-Ping; Li, Xiao-Yu (Frontiers in Oncology, 2022)
Cancer is a major threat to human health and longevity. Chemotherapy is an effective approach to inhibit cancer cell proliferation, but a growing number of cancer patients are prone to develop resistance to various chemotherapeutics, including platinum, paclitaxel, adriamycin, and 5-fluorouracil, among others. Significant progress has been made in the research and development of chemotherapeutic drugs over the last few decades, including targeted therapy drugs and immune checkpoint inhibitors; however, drug resistance still severely limits the application and efficacy of these drugs in cancer treatment. Recently, emerging studies have emphasized the role of circular RNAs (circRNAs) in the proliferation, migration, invasion, and especially chemoresistance of cancer cells by regulating the expression of related miRNAs and targeted genes. In this review, we comprehensively summarized the potential roles and mechanisms of circRNAs in cancer drug resistance including the efflux of drugs, apoptosis, intervention with the TME (tumor microenvironment), autophagy, and dysfunction of DNA damage repair, among others. Furthermore, we highlight the potential value of circRNAs as new therapeutic targets and prognostic biomarkers for cancer.